Adenosine 5'-phosphosulphate reductase is regulated differently in Allium cepa L. and Brassica oleracea L. upon exposure to H2S - Durenkamp, Mark (Journal of experimental botany, 2007)
The reduction of adenosine 5'-phosphosulphate (APS) by APS reductase (APR) is considered to be one of the rate-limiting steps in the assimilation of sulphur in plants. In order to identify the mechanisms of regulation of this enzyme, the impact of atmospheric H2S exposure on mRNA expression, protein level, and activity of APR was studied in two species (Allium cepa L. and Brassica oleracea L.) with different physiological responses to H2S exposure. As expected, H2S exposure resulted in a rapid increase in thiol compounds in the shoot of both species. There was a substantial increase in total sulphur content in shoots of A. cepa, whereas it was hardly affected or even slightly decreased in B. oleracea. Sulphate uptake was only marginally affected in A. cepa, whereas it was strongly decreased in B. oleracea upon H2S exposure. Furthermore, H2S exposure resulted in a down-regulation of APR activity in shoot and roots of both species, which was probably mediated by a transcriptional mechanism of regulation by thiols, since mRNA levels also decreased. However, in contrast to B. oleracea, APR protein level was not affected by H2S exposure in A. cepa. The reduction in APR activity in onion was therefore achieved by an additional as yet unknown post-translational regulation. These results demonstrate that not only the physiological response to H2S, but also the molecular mechanisms of regulation of APR differ in the two species